Drugs affecting the newborn body weight, length and head circumference at birth - Milosavljević, Jovana; Kočović, Aleksandar; Pejčić, Ana; Milentijević, Milica; Arsenijević, Petar; Milosavljević, Miloš; Janković, Slobodan (Archives of Pharmacy, 2022)
Newborn anthropometric measures at birth are important indicators of neonatal health, infant survival and childhood morbidity. Our aim was to identify factors that significantly influence newborn birth weight, length, and head circumference. This was a cohort study with combined retrospective and prospective data collection conducted on pregnant women whose pregnancy was monitored at the Clinic for Gynecology and Obstetrics at University Clinical Centre Kragujevac, Serbia. The influence of potential factors on birth weight, length, and head circumference was evaluated by multiple linear regression analysis. The study included 320 pregnant women with an average age of 30.35±5.50 years and 332 newborns (12 pairs of twins). We identified four factors with a significant negative effect on newborn birth weight, among which were use of methyldopa (B= –145.561;p=0.033) and corticosteroids during pregnancy (B= –287.921;p=0.001). Negative effect on newborn head circumference at birth inter alia had use of corticosteroids (B= –0.961;p=0.003) and antibiotics during pregnancy (B= –0.547;p=0.009), while the use of corticosteroids also showed a significant negative effect on birth length in the final multiple linear regression model (B= –1.818;p=0.000). The summary of product characteristics of corticosteroids warns that they may increase the risk of intra-uterine growth retardation when administered for prolonged periods or repeatedly during pregnancy, while the effects of methyldopa and antibiotics on fetal development are not well known. Clinicians should pay special attention to pregnant women who use corticosteroids, methyldopa and antibiotics during pregnancy in order to prevent low anthropometric measures of newborns at birth.